Soft Robots: Computational Design, Fabrication, and Position Control of a Novel 3-DOF Soft Robot - Martin Garcia; Andrea-Contreras Esquen; Mark Sabbagh; Devin Grace; Ethan Schneider; Turaj Ashuri; Razvan Cristian Voicu; Ayse Tekes; Amir Ali Amiri Moghadam (Machines, 2024)
This paper presents the computational design, fabrication, and control of a novel 3-degrees-of-freedom (DOF) soft parallel robot. The design is inspired by a delta robot structure. It is engineered to overcome the limitations of traditional soft serial robot arms, which are typically low in structural stiffness and blocking force. Soft robotic systems are becoming increasingly popular due to their inherent compliance match to that of human body, making them an efficient solution for applications requiring direct contact with humans. The proposed soft robot consists of three soft closed-loop kinematic chains, each of which includes a soft actuator and a compliant four-bar arm. The complex nonlinear dynamics of the soft robot are numerically modeled, and the model is validated experimentally using a 6-DOF electromagnetic position sensor. This research contributes to the growing body of literature in the field of soft robotics, providing insights into the computational design, fabrication, and control of soft parallel robots for use in a variety of complex applications.